Dengue RNA detection and seroprevalence in blood donors during an outbreak in the São Paulo State, Brazil, 2016. Issue 6 (30th October 2020) - Slavov, Svetoslav N.; Santos, Elaine V.; Hespanhol, Marta R.; Rodrigues, Evandra S.; Haddad, Rodrigo; Ubiali, Eugênia M. A.; Covas, Dimas T.; Kashima, Simone
Abstract: Most dengue virus (DENV) infections remain asymptomatic. This increases the risk of DENV transfusion transmission (TT‐DENV) during outbreaks. We evaluated DENV viremia in 8475 blood donations assembled in minipools for the presence of DENV RNA. The tested samples were obtained between February and May, 2016, during a large DENV outbreak in Ribeirão Preto city, northeast region of the São Paulo State, Brazil. The DENV RNA + samples were serotyped and screened for DENV NS1. We also tested a significant number of plasma samples ( n = 372) to estimate the DENV seroprevalence among blood donors in the region. We detected three DENV RNA + samples in the tested blood donations ( n = 3/8475, 0.04%). From these, two samples were further serotyped as DENV‐1 and one sample as DENV‐2. All DENV RNA positive samples were negative for anti‐DENV IgG, indicating the presence of primary acute infection. Moreover, two of the DENV RNA + samples were also NS1 antigen positive (antigenemia). The anti‐DENV IgG seroprevalence among blood donor population was 50.8% ( n = 189/372). Our results are in accordance with the presence of DENV primary infection in blood donors which can lead to transfusion transmission of the infection to recipients. Measures to exclude such donors should be adopted to prevent TT‐DENV.